Bioactivity of lufenuron against Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - Muhammad Yasir; Muhammad Sagheer; Abbas, Saqi Kosar; ul-Hasan, Mansoor; Ahmad, Saeed; Muhammad Ijaz (Penerbit Universiti Kebangsaan Malaysia, 2019)
Red flour beetle, Tribolium castaneum is a serious pest of stored grain commodities. A laboratory study was conducted for evaluating the sub-lethal effects of a chitin synthesis inhibitor, lufenuron at concentrations of 0.02, 0.04 and 0.08 ppm against two strains of T. castaneum. Lufenuron caused significant effects on larval mortality, larval duration before pupae, larval weight, pupae and adult emergence. When these adults were allowed to oviposit on untreated wheat flour, their fecundity and egg hatchability was reduced to a larger extent at all the tested concentrations as compared to control treatment. Further, subsequent development of F1 larvae, pupae and adults were also severely prohibited. Our findings show that lufenuron can be a potential product for pest management in mills, warehouses and food storage facilities.